THE EFFECT OF RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), AND EARNINGS PER SHARE (EPS) ON STOCK PRICES OF MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Iqlima Azhar; Tuti Meutia (Proceeding International Seminar of Islamic Studies, 2022)
: This study aims to determine the effect of Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS) on the stock price of manufacturing companies on the Indonesia Stock Exchange. The type of data in this study is quantitative data using secondary data. The research data is the company's annual financial report published through www.idx.co.id. The population in this study are all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period totalling 42 companies. The research sample was selected using a purposive sampling method to obtain a total sample of 20 companies. The data analysis method in this study uses multiple linear regression analysis with a significance level of 5% and is processed using SPSS. The results of this study indicate that: Return on Equity has a significant effect on Manufacturing Company Stock Prices on the Indonesia Stock Exchange, Net Profit Margin has no significant effect on Stock Prices of Manufacturing Companies on the Indonesia Stock Exchange, Earnings per Share have a significant effect on the Stock Prices of Manufacturing Companies on the Indonesia Stock Exchange, Return on Equity, Net Profit Margin, and Earnings per Share have a significant effect on the Stock Prices of Manufacturing Companies on the Indonesia Stock Exchange.Keywords: Stock Price, ROE, NPM, EPS